MODAL SOSIAL: SEBUAH PERSPEKTIF TERHADAP PROBLEMATIKA ANAK JALANAN DI KOTA KUPANG - Magor, Helena Dowibrin; H. Molan, Kristianus Simon; T. Sius, Karolus; Nyong, Franz (Politeknik STIA LAN Makassar, 2024)
The problem of street childern in the city of kupang is increasingly worrying where the number of street childern has increased very significantly in the last view years from 2017-2023, amoung to 1,257 childern. This had led to the emergence of the view that this probleme must be addresed wisely by various parties such as the goverment, NGOs, and the community. Tha aim of the research is to identify and analyze it comprehensively. Problem of street childern in the city of kupang using the social capital perspective proposed by putnam with increator of social networs, social norms and social trust. The research method used in the research is descriptive kualitative with data collection procedures of observation, in-depth interviews and documentation. Base on the result the research found that in heandling the problem of street childern, communication in the social network built beetwen the street childern and 2.SM in the city of kupang has not been carried out effectively and in depth, social norms in the manegement of resourch management have been carried out with honesty but are not yet fully effective and level of social trust beetwen actors in handling street childern in the city of kupang are still very small. In line with this reseacrh, the prolem of the street childern can be overcome if actor elements such us goverment, society and NGOs form effective communication patterns in implementing policies with social media well and are able to build trust beetwen the handling policy actors, street childern of kupang city supported by adequate resources